ANALISIS KOMPARASI SEKTOR PERIKANAN LAUT PRESPEKTIF EKONOMI DI WILAYAH PESISIR JAWA TIMUR (Studi Kasus Kab Lamongan, Kab Trenggalek dan Kab Banyuwangi) - Totok Hendarto (BALANCE: Economic, Business, Management and Accounting Journal, 2008)
Indonesia consists of 70% sea, a big potential of diversity, 6.1 million ton per year of fishery, and 57% have utilized. UU No.31, 2004 said that fishery resources potential should be managed well. While UU No.32, 2004 said that authority of fishery management should be decentralized to province/regency-city government as broad as to increase people’s welfare and local competition. The study has done by quantitative and qualitative phenomenological by survey method. Globally, fishery resources utilization in coastal area management perspective caused development disparity in East Java Province. The characteristic of north coastal area was more opened and has high economic activity network. It showed economical dynamic which higher than others. Planning and arranging area development strategy should be directed to maturing organization and revitalization its function. In the south coastal area, according to its diversity,resources condition, decentralization maturity level, and region authority, it should be directed to investment which bigger both the number of variety and the number of infrastructure unit, and facility of area development. Key words: comparition,fishery management.